PENGARUH PERBEDAAN INDIVIDUAL TERHADAP KEAHLIAN DALAM END USER COMPUTING - Wisnubroto, Petrus (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
The model was tested to permanent employee of Private Colleges wich have im-plemented on line computerization system, with 202 samples wich categorized into cle-rical group as much as 91 samples, non clerical group as much as 111 samples, total ob-served group as much 202 samples. Problem this research do the demographic factors (age, sex, education, experience) and personality (computer anxiety, computer attitudes, math anxiety) have a significant influence skill in end user computing. The test is done in four steps i. e, non respones bias test, reliability and validity test, inter variable correla-tion, hypothesis test with multiple regression and the data analysis is conducted by using SPSS program version 1.0 for windows. The reserach results showed that demographic factors (age, sex, experience) had directly effect into expertise in end user computing. Personality factors such com-puter anxiety (efar – anticipation) ; computer attitude (intimidation) had directly effect to expertise in end user computing. A quite surprising result was demographic factor of education, and personality factors of computer attitude (pessimism – optimism); of math anxiety was undequately significant to expertise in end user computing. For increasing work’s result in environment with introduction of new technology of on line computerization system above, it is considered in decision making recruitmen hu-man resource with related to envollment, implementation of computer training and edu-cation for their permanent employee. The preparation of adequate faciloities was hopped to increase individual performance.